Analysis of Acceptance and Success of Digipos Aja Telkomsel in Kalimantan Region Using The Integration of UTAUT and DeLone & McLean Models - Febriana Hestika Mirandi; Dodie Tricahyono (International Journal of Social Service and Research, 2023)
The current development of technology and information is driving various business sectors to undergo transformation. Telkomsel continues to strive to enhance ease in providing digital connectivity support solutions. One of these efforts is the establishment of a supply chain ecosystem through the management of Telkomsel resellers by introducing the Digipos Aja application. This research aims to identify factors that influence acceptance and success of implementing Digipos Aja. It employs variables from the Unified Theory of Acceptance and Use of Technology (UTAUT) model and Delone and McLean IS Success model. Quantitative method involves collecting data about usage frequency, user satisfaction levels, and benefits received through a questionnaire distributed to 400 resellers using DigiPOS Aja in the Kalimantan region. Quantitative data is analyzed using Partial Least Square (PLS) and Structural Equation Modeling (SEM) with the data processing tool SmartPLS. The research results indicate that two variables, System Quality and Service Quality, are not significant in relation to Continuance Intention.